Technical stroke regulations discriminate pacing effectiveness during a 5-km indoor pool race - Bouvet, A.; Pla, R.; Nicolas, G.; Bideau, N. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To investigate technical regulation mechanisms of long-distance swimmers that differentiate optimal pacing strategies and the underlying kinematic parameters.